Produktivitas Ayam Kampung Super (Joper) Pengaruh Rasio Lisin dan Metionin - Galih Cahyo Sukmo Sejati; Hanung Dhidhik Arifin; Roisu Eny Mudawaroch (Universitas Muhammadiyah Purworejo, 2019)
This study aims to determine the potential ratio of lysine and methionine in the ration to the productivity of super native chickens. The research was conducted at the Field Laboratory of Animal Husbandry Study Program at the University of Muhammadiyah Purworejo. The material used was 100 super native chickens, lysine, methionine, commercial feed, rice bran, milled yellow corn. The study used a completely randomized design (CRD) consisting of 5 treatments and 5 replications. The treatment given is the ratio of lysine: methionine which is 0: 0; 0.5: 0.5; 0.6: 0.4; 0.7: 0.3; 0.8: 0.2 of the amount of ration given. The parameters observed were feed consumption, PBBH, conversion, and feed efficiency. The data obtained were analyzed using Analysis of Variance, if there were differences continued with Duncan Test with a significance level of 5%. The results showed that the ratio of lysine and methionine in the ration had no significant effect (P> 0.05) on the consumption of BK as much as 50.074 g; 58,142 g; 56,144 g; 57,638 g; and 56,110 g. PK consumption had no significant effect (P> 0.05) of 6.422 g; 6,432 g; 6,210 g; 6,376 g; and 6,206 g. PBBH had no significant effect (P> 0.05) of 15.520 g; 15,490 g; 15,542 g; 15,530 g; and 15,544 g. The conversion value of BK has no significant effect (P> 0.05) with a value of 0.268; 0.266; 0.278; 0.268; and 0.276. PK conversion value has no significant effect (P> 0.05) with a value of 2.420; 2,410; 2,508; 2,434; and 2,508. The efficiency of BK has no significant effect (P> 0.05) with a percentage of 26.766%; 26,660%; 27,730%; 26,950% and 27,724%. PK efficiency had no significant effect (P> 0.05) with a percentage of 242.012%; 241,044%; 250.726%; 243,692% and 250,674%. The ratio of lysine and methionine in the ration has the potential to increase the productivity of native chicken. Research on the ratio of lysine and methionine needs to be done in the ration to increase the productivity of super native chickens.